Fluorescent Dye Labeled Iron Oxide/Silica Core/Shell Nanoparticle as a Multimodal Imaging Probe - Jang, Eue Soon; Lee, Seung Yong; Cha, Eui-Joon; Sun, In-Cheol; Kwon, Ick Chan; Kim, Dukjoon; Kim, Young Il; Kim, Kwangmeyung; Ahn, Cheol-Hee (SPRINGER/PLENUM PUBLISHERS, 2014)
To develop an MRI/optical multimodal imaging probe based on dye-conjugated iron oxide/silica core/shell nanoparticle, and investigate the distance-dependent fluorescence quenching through careful control of the distance between the iron oxide core and fluorescent dyes. Different size of core/shell nanoparticles were prepared by varying the silica shell width. PEGylation on the surface of silica shell was followed to improve the stability of particles in the physiological condition. In vitro cytotoxicity was evaluated by the MTT assay on a HeLa cell line and in vivo imaging of subcutaneous SCC7 xenografted mice was performed using MRI/optical imaging modalities. Diameter and zeta-potential of the nanoparticles were measured, and TEM images demonstrated the mono-disperse nature of the particles. Quenching efficiency of the dyes on the surface was nearly 100% in the smallest nanoparticle, while almost no quenching effect was observed for the largest nanoparticle. In vitro cytotoxicity showed nearly 90% cell viability at 0.15 Fe mg/mL, a comparable concentration for clinical use. The tumor area was significantly darkened after the nanoparticle injection due to the high transverse relaxivity value of the nanoparticles. Fluorescence signal was affected by the particle size due to the distance-dependent quenching/dequenching behaviour.
Keywords: OXIDE NANOPARTICLES; MAGNETIC-RESONANCE; PHOTOTHERMAL THERAPY; GOLD NANOPARTICLES; DRUG-DELIVERY; IN-VIVO; SHELL; CORE